Assessment and Validation of Syndromic Case Definitions for Respiratory Syncytial Virus Testing in a Low Resource Population. Issue 3 (March 2019) - Omer, Saad B.; Bednarczyk, Robert; Kazi, Momin; Guterman, L. Beryl; Aziz, Fatima; Allen, Kristen E.; Yildirim, Inci; Ali, S. Asad
Abstract : Standardized case definitions are needed in decision-making regarding respiratory syncytial virus control strategies, including vaccine evaluation. A syndromic case definition comprising of "wheeze or apnea or cyanosis" could be useful for community-based surveillance of moderate respiratory syncytial virus infection among young infants particularly in resource-limited settings. However, this definition showed modest specificity (29.2%–49.6%), indicating that community-based surveillance may need augmentation with other data. Abstract : Supplemental Digital Content is available in the text.